PENYELESAIAN SENGKETA KEPENGURUSAN KOPERASI PETANI IYO BASAMO - Wulan, Sari; Rusli, Benni; Adriaman, Mahlil (Universitas Ekasakti, 2023)
Cooperatives were founded on the principle of kinship, which is the pillar of the nation's economy which is expected to become the strength of the people's economy. Substitution of cooperative management can cause problems where the old management is compared with the new one, such as poor performance or negligence in carrying out their duties. The aim is to find out and understand the dualism settlement in the management of the Iyo Basamo Farmers Cooperative and the considerations of the Panel of Judges in the decision on the Iyo Basamo Farmers Cooperative dispute. This type of research is normative legal research with an approach that is literary, statutory and legal concept analysis. The conclusion and analysis of this study is that there is dualism in management due to the support of many parties who have backgrounds that are classified as important, especially in the government, as well as the cancellation of any decisions previously issued relating to the Iyo Basamo Farmers Cooperative